254 Paediatric deflection pathways: an enhanced triage process within the emergency department. (17th August 2022) - Baird, Rachel; Griffiths, Nathan
Abstract : Aims: As part of the Covid-19 recovery plan; nosocomial transmission of Covid-19 in hospital settings has been highlighted as a significant risk requiring mitigation. Reducing the number of patients attending departments and waiting in communal waiting and clinical areas has been highlighted as a way by which transmission of Covid-19 in hospital can be reduced. Our key objectives Reduce unnecessary Emergency Department attendances and those requiring clinical assessment within the unit Improve the flow of patients through the department to reduce the time each patient spends in the clinical area Provide safe clinical alternatives including, caring for the child at home. Influence parents and families to choose the most appropriate service for their child in the future In response in August 2020 we developed an enhanced triage deflection process with the aim to reduce the number of patients requiring clinical assessment on the PANDA Unit, subsequently reducing the patient footprint within the department and to improve adherence to social distancing national and trust guidance. Methods: On arrival to the emergency department; Children and Young People 0 – 15 years undergo an enhanced triage assessment by a Registered Children's Nurse who refer to condition led pathways to identify patients who are at a low, medium or high risk of serious illness. Children who are at low risk of serious illness and who do not meet the exemption criteria are discharged home from triage with advice for home management of common conditions whilst being given red flag symptoms to observe for. Children are assessed using condition led pathways based on NICE pathways. The pathways cover a range of illness and minor injury related presentations Results: Since August 2020 on average, we have sent home 22% of our patients from triage using this process with an average length of stay time of 13.1 minutes calculated from the time patients book in for triage and when they are being discharged home. We have seen a less than 4% return rate with no serious incidents identified and the median length of stay for returning patients is 102 minutes. We have received a positive response from parents and families with 92% reporting being very satisfied with the service provided and 69% stating that the advice given at triage would alter their future behaviors in accessing services or not. Conclusion: This process works to ensure that that patients attending the Emergency Department are seen and managed in the correct setting including their own home, improving patient safety and flow by reducing unnecessary attendances. We hope to change future behaviors of which service patients and their families access and will continue to monitor this retrospectively. As well as benefiting patients and their families this new way of working has had a positive impact on staff morale both within the Clinical and Nursing Team giving opportunities for professional development and job satisfaction.